Efficient Removal of Indigosol Blue Using Activated Carbon from Kepok Banana (Musa paradisiaca x balbisiana) Peels - Nurcahyo, Furqon Darma; Husna’ Putri Nur ‘Azizah; Atikah Khoiriyah Azzam; Mohammad Al Abi Aji Setiawan; Caesario Widya Atmaja; Rachmawati, Siti (BRIN Publishing, 2025)
Indonesia's textile industry has experienced significant growth, yet it faces environmental challenges from dye waste, such as Indigosol Blue, which is classified as hazardous and toxic, requiring special treatment. The use of activated carbon in the adsorption process has proven effective, and the Kepok banana (Musa paradisiaca x balbisiana) peel, with its high cellulose content, is a potential raw material for activated carbon. This research aims to produce adsorbents from Kepok banana peel, activated by HCl, to adsorb Indigosol Blue using an adsorption column. The production of activated carbon was conducted through carbonization and activation processes. HCl with a concentration of 37% was used as the activator, where the soaking process lasted for 24 hours, and the activation temperature was set at 90°C for 120 minutes. The activated carbon was characterized using UV-Vis Spectrophotometry, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR). Based on the results of SEM analysis that illustrates the differences in topography and morphology of kepok banana peel powder before and after activation using various concentrations of activating agents. The results of FTIR analysis, the presence of O-H and C-O bonds indicates that activated carbon derived from kepok banana peel has more polar characteristics. If the initial colorant is increased resulting in higher adsorption efficiency. The results of this study indicated that the optimal wavelength for the Indigosol Blue dye solution, was 624 nm. The best adsorption efficiency was 88.5%, and the maximum adsorption capacity of 0.24 mg/g was obtained with an adsorbent concentration of 30 ppm.